Editor's Note = Note du directeur [24, Fall 1989] - Kealey, Gregory S. (Labour / Le Travail, 1989)
The editor notes that various aspects of women's work are explored in the special issue. Also noted is the article on historical researchers' use of Privacy Act, including issues arising from Access to Information and Privacy Acts. The editor updates on his own experiences in this regard.
Keywords: INFORMATION policy; WOMEN -- Employment

The War Series, Part 1, 1939-1941 - Kealey, Gregory S.; Whitaker, Reginald (R.C.M.P. Security Bulletins, 1989)
From its inception in 1919-1920 the Royal Canadian Mounted Police security service compiled periodic reports on "subversive" activity in Canada, which were circulated to the Prime Minister and Cabinet. Through use of Canada's Access to Information legislation Gregory S. Kealey and Reg Whitaker have acquired copies of the extant Bulletins, which are now held by the Canadian Security Intelligence Service....This volume covers the early years of World War II when the Communist Party of Canada was illegal and many CPC leaders were interned. --Publisher's description
Keywords: 20th century; Canada; Communism; History; Internal security; Royal Canadian Mounted Police (RCMP); Subversive activities; WORLD War, 1939-1945

Book Notes [24, Fall 1989] - Palmer, Bryan D.; Kealey, Gregory S.; VDP (Labour / Le Travail, 1989)
The article briefly reviews "Canadian Corporate Power," by Henry Veltmeyer, "People and Places: Studies of Small Town Life in the Maritimes," edited by Larry McCann, "Schooling and Scholars in Nineteenth-Century Ontario," by Susan E. Houston and Alison Prentice, "No Bleeding Heart: Charlotte Whitton, A Feminist on the Right," by P.R. Rooke and R.L. Schnell, "The Memoirs of Giovanni Veltri," edited by John Potestio, "Feminist Research: Prospect and Retrospect," edited by Peta Tancred-Sheriff, "Waterfront Warlord: The Life and Violent Times of Hal C. Banks," by Peter Edwards, "Free Trade and the Future of Women's Work: Manufacturing and Service Industries," by Marjorie Griffin Cohen, "The History of the Ontario Liquor Board Employees' Union," by Beverly Dalys, "Labour Law Under the Charter: Proceedings of a Conference." sponsored by the Industrial Relations Centre, School of Industrial Relations and Faculty of Law, Queen's University, "The State of the Art in Industrial Relations," edited by Gerard Hébert, Hen C. Jain, and Noah M. Meltz, "Case Critical: The Dilemma of Social Work in Canada," by Ben Carniol, "From Culture to Power: The Sociology of English Canada," by Robert J. Brym, with Bonnie Fox, "On the Archival Heritage of the Finnish Canadian Working-Class Movement: A Researcher's Guide and Inventory to the Finnish Organisation of Canada Collection at the National Archives of Canada," by Edward W. Laine, "On the Line: Essays in the History of Auto Work," edited by Nelson Lichtenstein and Stephen Meyer, " To Toil the Livelong Day' : Women at Work, 1780-1980," edited by Carol Groneman and Mary Beth Norton, "Hard Times in Paradise: Coos Bay, Oregon, 1850-1985," by William G. Robbins, "Working Lives: An Oral History of Rhode Island Labor," edited by Paul M. Buhle, and "A History of Rhode Island Working People," edited by Paul Buhle, Scott Malloy, and Gail Salisbury, "Professionalism and Social Change: From the Settlement House Movement to Neighborhood Centers, 1886 to the Present," by Judith Ann Trolander, "Raising Less Corn and More Hell: Midwestern Farmers Speak Out," by Jim Schwab, "The Party of Fear: From Nativist Movements to the New Right in American History," by David H. Bennett, "The American Perception of Class," by Reeve Vannenun and Lynn Weber Cannon, "Prudent Revolutionaries: Portraits of British Feminists Between the Wars," by Brian Harrison, "Trade Unions and the New Industrialization of the Third World," edited by Roger Southall, "Pass Controls and the Urban African Proletariat," by Doug Hindson / reviews by Bryan D. Palmer -- " First Days, Fighting Days. Women in Manitoba History," edited by Mary Kinnear / review by VDP [see editor's note for correction made in no. 25 (Spring 1996), page 6] -- "The Road from Coorain," by Jill Ker Conway / review by Gregory S. Kealey.

Class, Community, and the Labour Movement Wales and Canada, 1850-1930 - Llafur (Society) (Past CCLH Publications, 1989)
This collection of essays stems from a joint conference held at the University College of Wales at Aberystwyth by the Committee on Canadian Labour History and the Society for the Study of Welsh Labour History. An Introduction by David Montgomery places the essays in a broader international perspective. Contributors from Wales include John Williams, Christopher Turner, Merfyn Jones, Dot Jones, and Deian R. Hopkin. Canadian essays are by Craig Heron, Robert Babcock, Bruno Ramirez, Allen Seager, Linda Kealey, Varpu Lindstrom-Best, and Gregory S. Kealey. The volume includes photographs, maps and tables. --Publisher's description. Contents: The rise and decline of the Welsh economy, 1890-1930 / John Williams -- Labour and industrial capitalist development in the North Atlantic Region, 1880-1920 / Robert Babcock -- The second Industrial Revolution in Canada, 1890-1930 / Craig Heron -- Conflicts of faith? / Christopher Turner -- Serfdom and slavery / Dot Jones -- Of men and stones / Merfyn Jones -- Migration and regional labour markets, 1870-1915 / Bruno Ramirez -- No special protection--no sympathy / Linda Kealey -- Miners'struggles in Western Canada, 1890-1930 / Allan Seager -- Canadian mining towns / Varpu Linstrom-Best -- The parameters of class conflict / Gregory S. Kealey -- The great unrest in Wales, 1910-1913 / Deian R. Hopkin. Papers from a conference of Committee on Canadian Labour History and Llafur, the Society for the Study of Welsh Labour History, held in April 1987 near Newtown in Mid-Wales.
Keywords: 19th century; 20th century; Canada; Congresses; Congresses. Labor movement; Congresses. Working class; Economic conditions; History; Social conditions; Wales; Working class